Cognitive-enhancing drugs in the healthy population: Fundamental drawbacks and researcher roles - Choy, Tsee Leng (Cogent OA, 2015)
The use of pharmacological cognitive enhancers (PCEs) in the healthy population is a controversial topic with numerous and expansive repercussions. By outlining common proponent arguments on the current PCE state of affairs, the definition of normality, and the complex regulation of PCEs, this article addresses why the mainstream use of PCEs in the healthy population is still disadvantageous overall. In this respect, the influence and roles of researchers to the society are emphasized in bringing the focus back to the fundamental issues, which is crucial in deciphering its controversy and avoiding costly societal, research credibility and ethical implications.